2021
DOI: 10.18665/sr.314912
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with Primary Sources: Looking at the Support Needs of Instructors

Abstract: Ithaka S+R's Teaching Support Services Program investigates the teaching practices and support needs of collegiate instructors. Our most recent project in this program, "Supporting Teaching with Primary Sources," focused on identifying how to effectively support instructors and their students find, access, and use primary sources in classroom environments.Encounters with primary sources-historical or contemporary artifacts that bear direct witness to a specific period or event-are central to the pedagogy of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Pitt Ithaka local report 38 as well as the Ithaka Capstone Report 39 on teaching with primary sources showed that instructors valued the commentary provided by librarians and archivists regarding provenance, background, creators, methods of production, dissemination, and inclusion or exclusion into the institution's special and archival collections. Such practices dovetailed with course readings and lecture content through the curatorial role librarians and archivists fulfilled as they selected materials and design or collaborated on creation of engagement activities to meet instructional outcomes for specific courses.…”
Section: Cultural Competency With Primary Sourcesmentioning
confidence: 99%
“…The Pitt Ithaka local report 38 as well as the Ithaka Capstone Report 39 on teaching with primary sources showed that instructors valued the commentary provided by librarians and archivists regarding provenance, background, creators, methods of production, dissemination, and inclusion or exclusion into the institution's special and archival collections. Such practices dovetailed with course readings and lecture content through the curatorial role librarians and archivists fulfilled as they selected materials and design or collaborated on creation of engagement activities to meet instructional outcomes for specific courses.…”
Section: Cultural Competency With Primary Sourcesmentioning
confidence: 99%
“…Educators who teach (with) primary sources will benefit from engaging with archivists early in the course development process (Tanaka et al 2021). As you design courses with CDHA materials, you should not hesitate to reach out to the CDHA team of curators, who will provide essential insights about how collections were put together, what was left out, and what remains to be collected.…”
mentioning
confidence: 99%
“…Educators who teach (with) primary sources will benefit from engaging with archivists early in the course development process (Tanaka et al. 2021).…”
mentioning
confidence: 99%